2018
DOI: 10.1101/243485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of ribosomes and release factors during translation termination inE. coli

Abstract: Release factors RF1 and RF2 promote hydrolysis of peptidyl-tRNA during translation termination.The GTPase RF3 promotes recycling of RF1 and RF2. Using single molecule FRET together with ensemble kinetics, we show that ribosome termination complexes that carry two factors, RF1-RF3 or RF2-RF3, are dynamic and fluctuate between non-rotated and rotated states, while each factor alone has its distinct signature on the ribosome dynamics and conformation. Dissociation of RF1 depends on peptide release and the presenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…By contrast, biochemical experiments showed that locking RF1 on the ribosome by inactivating its catalytic motif (GGQ-> GAQ) prevented RF1 recycling by RF3 from the pre-hydrolysis ribosome (Koutmou et al, 2014). These and other (Adio et al, 2018) observations indicate that peptidyl-tRNA hydrolysis is critical for RF1 dissociation, likely due to propensity of deacylated tRNA for exiting the P site and sampling the P/E hybrid state via spontaneous intersubunit rotation (Moazed and Noller, 1989). Nevertheless, RF3 is dispensable for growth of Escherichia coli (Grentzmann et al, 1994;Mikuni et al, 1994), and its expression is not conserved in bacteria (Leipe et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…By contrast, biochemical experiments showed that locking RF1 on the ribosome by inactivating its catalytic motif (GGQ-> GAQ) prevented RF1 recycling by RF3 from the pre-hydrolysis ribosome (Koutmou et al, 2014). These and other (Adio et al, 2018) observations indicate that peptidyl-tRNA hydrolysis is critical for RF1 dissociation, likely due to propensity of deacylated tRNA for exiting the P site and sampling the P/E hybrid state via spontaneous intersubunit rotation (Moazed and Noller, 1989). Nevertheless, RF3 is dispensable for growth of Escherichia coli (Grentzmann et al, 1994;Mikuni et al, 1994), and its expression is not conserved in bacteria (Leipe et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Following peptide release, RF1 or RF2 must dissociate from the ribosome to allow the ribosome and release factor to recycle. While structural studies have provided snapshots of some peptidyl-tRNA hydrolysis steps (reviewed in (Dunkle and Cate, 2010;Korostelev, 2011;Ramakrishnan, 2011;Rodnina, 2018;Youngman et al, 2008), recent biophysical and biochemical findings suggest a highly dynamic series of termination events (Adio et al, 2018), which have not been structurally visualized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein release factors have different evolutionary origins in different domains of life (Vestergaard et al 2001), and auxiliary factors, like those that recycle the joined ribosomal subunits after termination, are also of independent evolutionary origin (Zavialov et al 2005). Moreover, termination factors are sophisticated protein catalysts (e.g., Adio et al 2018) that cannot exist until translation itself is sophisticated. Such considerations suggest that translation termination also took its final form late, after separation of life's domains (Burroughs and Aravind 2019).…”
Section: Sgc-like Codes Are In Multiple Upper Tailsmentioning
confidence: 99%
“…Again, the process follows Landauer's principle: release factor 3 promotes recycling of release factors 1 and 2. To this aim, it binds in the GTP-bound state and can rapidly dissociate without GTP hydrolysis from termination complex carrying release factor 1, while in the absence of release factor 1, release factor 3 is stalled on ribosomes if GTP hydrolysis is blocked (Adio et al, 2018).…”
Section: Accurate Template Recognition During Translation and Antibiomentioning
confidence: 99%